Challenges of Measuring Moral Distress in the Context of Social and Health Care - Kuip, Mänttäri-van der (Sage Publications Ltd, 2017)
Defining the experience of moral distress in all its complexity, and building a valid instrument to measure it, has presented a major challenge for researchers conducting surveys on this issue. The various and partially inadequate definitions of the concept have led to varying and sometimes even controversial ways of measuring it. This case study centers on the challenges that I faced when I was studying experiences of moral distress among professional social workers. The study is based on an empirical article aimed at shedding light on the experiences of moral distress among social workers with specific focus on the role of perceived resource insufficiencies in explaining these experiences. The empirical article utilized survey data collected as a part of my dissertation project on the capabilities and well-being of professional social workers. In this case study, I focus in particular on the methodological and theoretical challenges presented by the conceptualization, operationalization, and measurement of this phenomenon. Here, moral distress is defined as work-related distress experienced by different professionals in the field of social and health care. It develops when a person is not able to practice in a way he or she considers morally appropriate, owing, for example, to personal, institutional, or organizational obstacles. It is measured with a binary construct consisting of two elements: one measuring the experience of moral distress, that is to say the restricted capability to practice in full accordance with ones moral code; and the other the impaired well-being related to this incapability.